Estudo fitoquímico, toxicológico e farmacológico das raízes de Cereus Jcaru DC. (Cactaceae) - Santos, Edvania Emannuelle Pinheiro (2024)
Research on natural products plays a crucial role in discovering substances with therapeutic potential. In the semi-arid region of Northeast Brazil, the roots of Mandacaru (Cereus jamacaru) are used in traditional medicine to treat certain types of inflammation. Therefore, the aim of this study was to conduct a phytochemical analysis of the roots of this plant and evaluate its toxicity, as well as its anti-inflammatory, antinociceptive, and antipyretic activities. The collection was carried out in Esperança, Paraíba, and after drying and grinding, the crude hydroethanolic extract (CHE) was obtained. This extract was fractionated and subjected to high-performance liquid chromatography coupled with mass spectrometry (HPLC-MS) and molecular networking analysis via the GNPS platform (The Global Natural Product Social). The presence of a molecular family of saponins was confirmed in the methanol-water fraction (MWF), including jamacaruside A and analogs of jamacaruside B, previously isolated from the cladodes of C. jamacaru. In the pharmacological phase, the acute toxicity assay of MWF was performed at a dose of 2000 mg/kg, evaluating water and food consumption, weight gain, behavior, and biochemical and hematological assessment of the tested animals. Antinociceptive activity (through tail immersion tests, acetic acid-induced abdominal writhing, and formalin test), anti-inflammatory activity (paw edema and carrageenan-induced peritonitis assays, and air pouch model), and antipyretic activity were also performed. In all these assays, MWF was used at doses of 50, 100, and 200 mg/kg. MWF showed no acute toxicity or significant changes in hematological and biochemical parameters. In antinociceptive activity, MWF demonstrated efficacy at doses of 50, 100, and 200 mg/kg in all tests conducted. Regarding anti-inflammatory activity, MWF was effective in all assays and doses tested, with results similar to dexamethasone at the highest dose (200 mg/kg). As for antipyretic activity, MWF reduced temperature at all doses after 30 minutes. The results obtained corroborate the traditional use of Mandacaru as an analgesic, anti-inflammatory, and antipyretic agent, suggesting that the presence of saponins in MWF is associated with these effects. Thus, C. jamacaru proves to be a promising source in the search for new therapeutic agents.